2008
DOI: 10.1250/ast.29.215
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between two membranes of a Japanese drum

Abstract: Some drums have, typically, a hollow trunk (or a barrel) with a circular membrane at each of the two ends. In this type of drum structure, the two membranes interact with each other through the air between them inside the body. Even if the two membranes have an identical fundamental resonance frequency, the interaction results in two resonance frequencies. At the lower resonance, the two membranes vibrate in phase. Since the membranes must move the internal air, the frequency at the lower resonance is lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…4 Research into the coupling between the two heads of a Japanese drum, a wadaiko, has been performed by Suzuki and Hwang. 10 Their research concludes, "depending on the tension ratio of the membranes, the frequency and amplitude ratios of the coupled resonances change".…”
Section: Coupled Membranesmentioning
confidence: 99%
“…4 Research into the coupling between the two heads of a Japanese drum, a wadaiko, has been performed by Suzuki and Hwang. 10 Their research concludes, "depending on the tension ratio of the membranes, the frequency and amplitude ratios of the coupled resonances change".…”
Section: Coupled Membranesmentioning
confidence: 99%
“…The wood barrel is much more rigid and massive than the diaphragms. Previous study on the coupling between the two membranes of a Japanese drum through the air inside the wood barrel, concentrating on the resonance frequency changes due to the coupling, has been investigated using semi analytical method [1]. In that study, the wood barrel wall was treated rigid, and the membrane bending stiffness was neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have been reported on the resonance frequencies of Japanese drums [7][8][9]. Even though the structure of the nagado-daiko is very simple, the coupling of the two diaphragms complicates the distribution of the resonance frequencies [10,11]. To avoid this problem, one of the two diaphragms of a 0.48 m diameter nagado-daiko was removed and the resonance frequencies of the remaining diaphragm were compared to those of numerically-calculated frequencies.…”
Section: Introductionmentioning
confidence: 99%